PERSEPSI BIRO PERJALANAN WISATA TERHADAP KENAIKAN HARGA TIKET MASUK MENUJU TAMAN NASIONAL BALI BARAT - Gusti Ayu Putu Inten Pratiwi Kalpika; I Made Adikampana (JURNAL DESTINASI PARIWISATA, 2016)
Abstract                        This research is conduct in West Bali National Parks and focus on tour operator perception on price increase of entrance fee. The purpose of this study was to determine the perception of a tour operator towards the price increase of entrance fee to the West Bali National Park. Data collection was done by observation, interviews, questionnaires and literature study. The method used in this research is to analyze the data with the Likert Scale and described qualitatively.The results show that a tour operator on average have a negative perception or refuse towards the price increase of entrance fee to the West Bali National Park. That case cause by the price of entrance fee increase highly with amount is 1,150% for international tourist and 700% for domestic tourist. The price increase of entrance fee is not suitable and not increased in stages. Besides that, the price increase of entrance fee will influence the revenue of tour operator and also will influence tourist visits because there are many similar destination package tour what offer the cheaper price.